Lipid Lowering and Antioxidant Activities of Methanolic Extract of Ficus hispida Linn. Fruits in Cholesterol Fed Rats - Islam, M. E.; Hosaain, M. S.; Dutta, S.; Parvin, M. S. (Journal of Scientific Research, 2018)
The present study was designed to evaluate the effect of fruits extracts (Ficus hispida) on serum lipids and antioxidant status in hypercholesterolaemic rats. Hyperlipidemia was induced by feeding high fat diet for 28 days and was evidenced by elevated levels of serum triglycerides (TG), serum LDL cholesterol and decreased serum HDL cholesterol. Oxidative stress was measured by determining the activity of antioxidant enzymes like superoxide dismutase (SOD), catalase (CAT), and amount of thiobarbituric acid reactive substances (TBARS) in liver homogenate of experimental rats. In hypercholesterolaemic rats, crude methanolic extract (CME) consumption had no effect on HDL-cholesterol, yet it showed a marked hypolipidaemic action, decreasing TG and LDL-cholesterol that had been increased after consuming the high-cholesterol diet. On the other hand, the concentration of TBARS decreased significantly, indicating decreased lipid peroxidation. In addition, the activities of catalase and SOD increased significantly in liver homogenate. The above evidence suggested that CME of the fruits of this plant can be a source of natural antioxidant that can reduce the plasma lipid (cholesterol) level and also decreases the lipid peroxidation.